The Influence of the National Civil Service Program for Fostering Prosperous Families (PNM MEKAAR) on the Income of the Poor in Dompu District - Nilam Dwi Maharani; Prayitno Basuki; Endang Astuti (Experimental Student Experiences, 2024)
This study aims to find out and to analyze how the MEKAAR PNM Program influences the income of the poor in Manggelewa District in 2019-2020. The research method used in this study is a descriptive quantitative approach with data collection techniques through questionnaires, observation, interviews and documentation. The technique used in taking samples from the population uses the slovin formula with an error rate of 10%. The results showed that the PNM MEKAAR program had a positive and significant effect on the income of the poor in Manggelewa District in 2019-2020.